Nākahi: The Matarahurahu Cult of the Snake - Moon, Paul (Te Kaharoa, 2011)
Throughout the nineteenth century, various Māori fusion religions flourished, combining elements of traditional Māori religion with those gleaned from the missionaries. One of the earliest of these was the Nākahi sect, which had its origins in the Ngāpuhi hapū of Matarahurahu.  This paper focuses on the Matarahurahu form of the sect. t assesses its main tenets, the role of personalities in leading the sect, and follows its development through to its demise.